PEMBANGUNAN LINGKUNGAN YANG HOLISTIK - Sitomurni, Amita Indah (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
Environment is now an important global current issue and as a factor thatmust be considered in the implementation of Indonesian nationaldevelopment. Entering globalization era, the condition of environment willbe one of the parameters required for a country to be accepted in theworld free trade community. Instead, a country with bad environment cantherefore be charged for a penalty, such as a limited export quota. Forthat reason, starting now, Indonesia should improve their environmentalcondition by implementing a good environmental management in order toattain the standard of a good environment. If Indonesia cannot achievethis goal, Indonesia will be used by other countries as their big market,without the ability of Indonesia to export their products. If the standard hasbeen fulfilled, Indonesia can be part of the world free trade community inwhich this is a benefit for Indonesia itself. Without lowering the pace ofdevelopment growth, national development through holistic environmentalmanagement would be a proper program to implement. This program isconsidering the impact of development to the environment and thisprogram was commencing by the Indonesian government since 1970.However, it seems that the holistic environmental development has notbeen running smoothly, especially at the soft sides of development, suchas people awareness, environmental law, law enforcement, arbitrarycommittee, community development, environmental information includingpeople rights to get those information, the role of non-governmentorganization, etc.By considering the importance of environmentaldevelopment in a holistic way to fulfill the globalization requirements, thispaper would be focused on the factors that may inhibit the nationaldevelopment. Those are factors that affect sustainability of environmentalfunctions. Solution to the problems may also generally be described.